2007
DOI: 10.1002/cm.20174
|View full text |Cite
|
Sign up to set email alerts
|

The effect of combined simulated microgravity and microgrooved surface topography on fibroblasts

Abstract: This study evaluated in vitro the differences in morphological behaviour between fibroblast cultured on smooth and microgrooved substrata (groove depth: 0.5 microm, width: 1, 2, 5, and 10 microm), which were subjected to simulated microgravity. The aim of the study was to clarify which of these parameters was more dominant to determine cell behaviour. Morphological characteristics were investigated using scanning electron microscopy and fluorescence microscopy in order to obtain qualitative information on cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 34 publications
3
25
0
Order By: Relevance
“…However, cells cultured on wider microgrooves of either 5 μm or 10 μm in width attached to the substrate just the same as on smooth surfaces, and there was no acceleration of calcification. Loesberg et al (9,10) used the same size microgrooves as Matsuzaka et al (11) and suggested that cell differentiation was accelerated on microgrooves of 1 μm to 2 μm in width, because cells were suspended in the groove as a cellular bridge and exposed receptors existing on the cell membrane, making it easier to get molecular signals such as dexamethasone into the culture medium and cause (or induce) the cells to differentiate into mature osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…However, cells cultured on wider microgrooves of either 5 μm or 10 μm in width attached to the substrate just the same as on smooth surfaces, and there was no acceleration of calcification. Loesberg et al (9,10) used the same size microgrooves as Matsuzaka et al (11) and suggested that cell differentiation was accelerated on microgrooves of 1 μm to 2 μm in width, because cells were suspended in the groove as a cellular bridge and exposed receptors existing on the cell membrane, making it easier to get molecular signals such as dexamethasone into the culture medium and cause (or induce) the cells to differentiate into mature osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the construction of an RPM a broad variety of sample enclosures are applied in RPM studies. This ranges from regular T25 flasks 31,32 to multiwell plates, 33 flask on slides, 34 or more dedicated devices. 35 Performing RPM studies, where the best simulation of microgravity is in the center of rotation of the two axes, has limits for the size of the preferred volume for the samples.…”
Section: Random-positioning Machinementioning
confidence: 99%
“…The rods would deflect in response to internal outwarddirected forces. Loesberg et al (2006Loesberg et al ( , 2007 used an isotropic microstructured surface in combination with hypergravity stress or simulated microgravity in a random positioning machine, RPM, to reveal the forces involved in cell orientation and morphology. Properties of standard plastic culture flasks are often taken for granted.…”
Section: Instruments and Methods To Study (Sub-) Cellular And Moleculmentioning
confidence: 99%